Clinico-pathological and haemato-biochemical responses in sheep fed with low and high levels of Brachiaria decumbens (Stapf) diet - Muniandy, Kalai Vaani (2021)
Brachiaria decumbens is a highly productive tropical grass for ruminant production that present abundantly in Malaysia. Nevertheless, there were many reports of sporadic outbreaks of general ill-thrift and deaths in ruminants attributable to the presence of steroidal saponins. As a result, farmers would not be able to utilise this grass as a feed source for ruminants. The present study aims to determine the clinico- pathology, haemato-biochemistry, and acute phase proteins (APPs) responses of sheep fed with low and high levels of B. decumbens diets at different time phases. A total of 30 six-month-old male Dorper cross sheep were randomly divided into three treatment groups consisted of 10 sheep each. Treatment 1 (control) sheep were fed with Pennisetum purpureum and concentrates as the basal diet, whereas Treatment 2 and 3 sheep were fed with low (10%) and high (60%) level of B. decumbents, respectively. The low and high levels were determined by evaluating the saponins concentration of B. decumbens at different percentages mixed with P. purpureum. This study was conducted in two phases consisted of the acute (7 days) and chronic (90 days) stages. Throughout the experiment, the clinical responses such as rectal temperature, respiratory rate, heart rate, and mucous membrane colour were evaluated and recorded. At day 0, 7, and 90, blood samples were collected via jugular venipuncture for complete blood count and acute phase proteins analysis, while cerebrospinal fluid (CSF) were collected via lumbar puncture at the lumbosacral site for haptoglobin (Hp) and serum amyloid A (SAA) analyses. At the end of 7th day (acute stage) and 90th day (chronic stage) of experiment period, five animals from each treatment group were slaughtered for post mortem examination and histopathology evaluation. There were no significant changes (p > 0.05) in the rectal temperature, pulse, and respiration rate throughout the study period except for the mucous membrane colour. T3 sheep demonstrated pale mucous membrane starting from day 60 until the end of experiment on day 90, whereas T2 sheep only showed pale mucous membrane at the chronic phase of the study which was on day 90. In addition, the haematology results revealed significant differences (p < 0.05) in the red blood cells (RBC), mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (MCHC), white blood cells (WBC), neutrophils, monocytes, eosinophils, basophils, platelets, and plasma proteins between groups. Except for packed cell volume (PCV), there were also significant differences in all haematology parameters at different time phases. All biochemistry parameters except creatinine revealed significant differences (p < 0.05) among treatment groups. There were significant differences in all parameters between phases. On the other hand, APPs results also showed significant differences (p < 0.05) in the serum Hp, serum SAA, and CSF SAA between groups and time. At necropsy, no apparent lesions were observed in all organs as well as no significant differences in the organ morphometric analysis. Histologically, both T2 and T3 sheep exhibited mild and moderate necrosis & degeneration; haemorrhages & congestion; and oedema of the liver and brain respectively. In summary, this study has established the effects of the low and high levels of B. decumbens diets and at different time phases in sheep which could provide valuable information to future B. decumbens research.